If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + -3 = 9x + 33 Reorder the terms: -3 + 5x = 9x + 33 Reorder the terms: -3 + 5x = 33 + 9x Solving -3 + 5x = 33 + 9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9x' to each side of the equation. -3 + 5x + -9x = 33 + 9x + -9x Combine like terms: 5x + -9x = -4x -3 + -4x = 33 + 9x + -9x Combine like terms: 9x + -9x = 0 -3 + -4x = 33 + 0 -3 + -4x = 33 Add '3' to each side of the equation. -3 + 3 + -4x = 33 + 3 Combine like terms: -3 + 3 = 0 0 + -4x = 33 + 3 -4x = 33 + 3 Combine like terms: 33 + 3 = 36 -4x = 36 Divide each side by '-4'. x = -9 Simplifying x = -9
| a=pi*r^2 | | X-10+y+3x=180 | | 3v^2+11=6v | | N+5.5=-4.5 | | 26*p=233 | | 10-5=25+10 | | 7x+25=3x+5 | | 4-(sec^2)(x)=0 | | bx=cforx | | 5x-7y=3x+y | | y=x^2+7x+32 | | A+15=233 | | 4r^2=64 | | ax+b=5(x-a) | | 10-(3z)=37 | | 5x=-12+4y | | X+2(x+3)=23 | | -56.1=-5.1f | | 16xy-18=16xy+8 | | 3xm=20 | | 4x+3=-5+21 | | [5(x+1)-3]+[4(x-2)+3]=[4(2x+3)-7] | | -80x=139 | | 2x+29=4(x+1) | | 14b=-565 | | 3-2=4 | | (2a^2+7a+1)-(3a^2+9a+7)= | | -3x+19=11 | | 8y-3=27 | | 7y-493y-50=80 | | 5(2+4r)=32 | | 18=2h+2 |